Architectural Models for Tactile Perception (diségno, 2024)
The article discusses the role that physical models play in the process of incorporating and breaking down perceptual and cognitive barriers in the communication and representation of historic-architectural heritage, also in relation to what international conventions and more recent regulatory guidelines indicate.In addition to the historically well-established purposes of the model as a design aid, other purposes have been added, such as providing a better understanding of spaces within orientation systems.In the field of cultural heritage enhancement, the use of the physical model is cited by several guidelines as a useful element in improving accessibility conditions for different types of users.The analog model can address both the ‘haptic narrative’ of the state of affairs and the narrative of hypothetical reconstructions of the same, thus being able to ‘speak’ not only to people with visual or cognitive disabilities, but to the totality of users.In this regard, the article illustrates a series of case studies that use the analogous model of architecture to overcome the role historically assigned to these artifacts, which involved an exclusively visual perception, by opening them up to a new level of sensory perception capable of increasing the degree of inclusiveness.
Keywords: accessibility; cultural heritage; perceptual barriers; communication; universal design